Exploration and Practice in the Construction and Dissemination of a Smart Urban Governance System: A Case Study of Baiyun District - Li, Feng; Chen, Chuanke; Dong, Yaoyi (Innovative Applications of AI, 2025)
In recent years, the deepening convergence of new-quality productive forces and the digital economy has furnished critical momentum for the modernization of China's governance system. By 2025, the value-added of core digital-economy industries is expected to exceed 10% of GDP [1], while artificial intelligence, data elements and related technologies are poised to empower virtually every sector. Responding to the national strategies of "Cyberpower" and "Digital China", the all-in-one government service platform has registered more than one billion real-name users; over 90% of administrative licensing items can now be processed online; 5G base stations nationwide have surpassed 3.3 million–more than 60% of the global total–and optical fibre together with 4G networks has reached every administrative village. Yet persistent problems–including redundant construction, high development costs, homogenised system functions, local protectionism, absent or fragmented standards, and inter-agency buck-passing-continue to constrain the high-quality development of digital government and smart cities.Anchored in the principles of "problem orientation, process re-engineering, data sharing and source governance", this paper examines Guangzhou Baiyun District's exploration and practice in constructing and disseminating its smart-city management system. We elaborate an innovative "1+4+N" governance architecture, unpack technological breakthroughs and standard-setting initiatives, and synthesise both achievements and remaining challenges. On this basis we derive a replicable pathway for county-level districts nationwide and propose targeted policy recommendations.Empirical evidence demonstrates that the "Baiyun Model" has markedly shortened administrative procedures, enhanced governance efficiency, reduced fiscal expenditure and enabled multi-stakeholder collaboration, thereby offering a paradigmatic reference for smart-city development across China.